2023
DOI: 10.5194/amt-2023-14
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Automated Online Field Instrument to Quantify the Oxidative Potential of Aerosol Particles via Ascorbic Acid Oxidation

Abstract: Abstract. Large-scale epidemiological studies have consistently shown that exposure to ambient particulate matter (PM) is responsible for a variety of adverse health effects. However, the specific physical and chemical properties of particles that are responsible for observed health effects, as well as the underlying mechanisms of particle toxicity upon exposure, remain largely uncertain. Studies have widely suggested that the oxidative potential (OP) of aerosol particles is a key metric to quantify particle t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Zhang et al (2022) showed that on average more than 90% of ROS in a photochemically aged mixture of primary combustion soot particles and naphthalene or β-pinene aerosols were short-lived. In addition, Utinger et al (2023) demonstrated the rapid decay of oxidizing components of (-pinene) secondary organic aerosol using a direct-to-reagent approach similar to that used here but with an ascorbic acid based assay, with simultaneous comparison to filter samples analyzed immediately after particle collection. The decay of particle-associated oxidizing species appears to occur in three phases, with one rapid (t 1/2 < 1 min), one medium decay phase (t 1/2 ~20 hrs.)…”
Section: Discussionmentioning
confidence: 94%
“…Zhang et al (2022) showed that on average more than 90% of ROS in a photochemically aged mixture of primary combustion soot particles and naphthalene or β-pinene aerosols were short-lived. In addition, Utinger et al (2023) demonstrated the rapid decay of oxidizing components of (-pinene) secondary organic aerosol using a direct-to-reagent approach similar to that used here but with an ascorbic acid based assay, with simultaneous comparison to filter samples analyzed immediately after particle collection. The decay of particle-associated oxidizing species appears to occur in three phases, with one rapid (t 1/2 < 1 min), one medium decay phase (t 1/2 ~20 hrs.)…”
Section: Discussionmentioning
confidence: 94%
“…10 Recent studies reported that storage (>7 days) of particles collected on the lter prior to analyses leads to a signicant underestimation of OP. [90][91][92] The soluble Mn concentration decreases with the OP DTT especially when comparing fresh WFs and WFs stored for 35 days in air at 20 °C. The solubility of Mn in the extracts of the tested WF samples plays an important role in the OP DTT measurements.…”
Section: Type Of the Extraction Solutionmentioning
confidence: 99%